Measurements of triple-differential cross sections for inclusive isolated-photon+jet events in p p collisions at √s=8TeV - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration.Measurements are presented of the triple-differential cross section for inclusive isolated-photon+jet events in p p collisions at s=8 TeV as a function of photon transverse momentum (pTγ), photon pseudorapidity (ηγ), and jet pseudorapidity (ηjet). The data correspond to an integrated luminosity of 19.7fb-1 that probe a broad range of the available phase space, for | ηγ| 25GeV. The measurements are compared to next-to-leading order perturbative quantum chromodynamics calculations, which reproduce the data within uncertainties.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)